USE OF N-TERMINAL NATRIURETIC PEPTIDE IN A REAL-WORLD SETTING OF PATIENTS ADMITTED WITH ACUTE DYSPNOEA AND THE IMPLICATION FOR TRIAGING PATIENTS IN THE EMERGENCY DEPARTMENT. (11th December 2014) - Carlsen, Christian M.; Mouridsen, Mette; Sajadieh, Ahmad; Køber, Lars; Nielsen, Olav W.
No abstract available